AB1066 DEFICIENCY OF ADENOSINE DEAMINASE 2: THE IMPORTANCE OF A DIAGNOSIS BEFORE IRREVERSIBLE DAMAGE. (June 2019) - Tronconi, Elena; Conti, Francesca; Cordelli, Duccio Maria; Volpi, Stefano; Gattorno, Marco; Pession, Andrea; Miniaci, Angela
Abstract : Background: In 2014, two independent groups, Zhou et al.(1) and Navon-Elkan et al.(2), described the first 34 patients with disease-associated mutations in adenosine deaminase 2 (ADA2 ). Objectives: To describe a new case of ADA2 deficiency (DADA2) in a 15 years old girl presenting with acute lower limb flaccid paralysis. Methods: Results: A 15 years old girl presented with acute lower limb flaccid paralysis. Neurologic exam showed peripheral deficit of the VII cranial nerve, absent motor activity at lower limbs with sensitive deficit. At physical examination she had marked and diffuse livedo reticularis. She underwent a brain and spinal magnetic resonance imaging (MRI) revealing multiple areas of signal abnormalities (T2 hyperintensity) in both thalamus and basal ganglia, small area in the spinal cord at C2-C3, at D10-D11 and L1 levels; these images were related to vascular damage. Blood exams showed high blood counts and inflammatory markers (C-reactive protein 16.76 mg/dl). Coagulation was normal, antiphospholipid and antinuclear antibodies were negative, immunological work-up showed normal immunoglobulins level, T and B phenotype. She received intravenous steroid and high-dose intravenous immunoglobulin. The constellation of findings led to clinical suspicion for DADA2, which was confirmed by low plasma ADA2 activity. For the presence of microhematuria, worsening proteinuria and hypertension, vascular ultrasound was performed with no evidence of renal artery stenosis. She underwent renal biopsy negative for glomerulonephritis, renal vasculitis and amyloidosis. Following the diagnosis of DADA2, she was initiated on etanercept 50 mg once weekly and she was able to taper steroid with normalization of inflammatory markers and improvement of skin rash. The girl is the second of 3 children, born from consanguineous parents of Italian origin. By the age of 1 she started suffering from fever, arthritis, pericarditis with elevated inflammatory markers and was diagnosed with systemic juvenile idiopathic arthritis (sJIA) and chronic disease anemia. At that time, she already presented livedo reticularis. She was treated with short term oral steroid and methotrexate with remission of fever and articular symptoms. At the age of 2 she had a convulsive crisis, polysomnography and brain MRI were negative. One year later she presented a convulsive status epilepticus, brain MRI was repeated and resulted negative. She was started on topiramate with no further crisis, treatment was stopped 2 years later. When she was 9, she was admitted for pancytopenia and she was diagnosed of Leishmania infection. The two siblings of the girl were tested for plasma ADA2 activity and both resulted deficient. The boy is 12 years old with mild development delay and a previous diagnosis of sJIA when he was 5. He was treated with steroid and Methotrexate with remission. The older sister is now 19 years old and she had an episode of erythema nodosum. Genetic test of all family members is still pending. Conclusion: Given the important morbidity, especially in consanguineous families, a high index of suspicion is needed for early diagnosis and precocious intervention, before persistent neurologic damage has been established. Our report describes for the first time a new neurological presentation as acute transverse myelitis in a patient with DADA2. References: [1] Zhou Q, Yang D, Ombrello AK, Zavialov A V., Toro C, Zavialov A V., et al. Early-Onset Stroke and Vasculopathy Associated with Mutations in ADA2. N Engl J Med. 2014; [2] Navon Elkan P, Pierce SB, Segel R, Walsh T, Barash J, Padeh S, et al. Mutant Adenosine Deaminase 2 in a Polyarteritis Nodosa Vasculopathy. N Engl J Med. 2014. Disclosure of Interests: Elena Tronconi: None declared, Francesca Conti: None declared, Duccio Maria Cordelli: None declared, Stefano Volpi: None declared, Marco Gattorno Grant/research support from: MG has received unrestricted grants from Sobi and Novartis, Andrea Pession: None declared, Angela Miniaci: None declared